A review of nitrogen removal for urban stormwater runoff in bioretention system - Osman M.; Yusof K.W.; Takaijudin H.; Goh H.W.; Malek M.A.; Azizan N.A.; Ghani A.A.; Abdurrasheed A.S. (MDPI, 2023)
best management practice; denitrification; leaching; nitrification; nitrogen; pollutant removal; runoff